Low band-gap weak donor–strong acceptor conjugated polymer for organic solar cell. Issue 120 (19th November 2015) - Shi, Zugui; Hoi Ka, Ivy Wong; Wang, Xizu; Vijila, Chellappan; Wang, Fei; Li, Gongqiang; Tjiu, Weng Weei; Li, Jun; Xu, Jianwei
Abstract : With an additional weak acceptor, the low band-gap donor–acceptor conjugated polymer displayed a remarkable power conversion efficiency of 5.36%. Abstract : By insertion of an additional weak acceptor into a donor–acceptor conjugated polymer backbone, a new weak donor–strong acceptor alternating copolymerPTTBOBT-DFBT was synthesized and it showed a low band-gap of 1.64 eV with a deep HOMO energy level (−5.44 eV). The bulk heterojunction (BHJ) solar cell fabricated from polymerPTTBOBT-DFBT displayed a remarkable power conversion efficiency (PCE) of 5.36% ( J sc = 11.04 mA cm −2, FF = 63.65%, V oc = 0.76 V).